Who Gets to Be in The Guild? Race, Gender and Intersecting Stereotypes in Gaming Cultures - Mejeur, Cody; Cote, Amanda (Loading, 2021)
While media studies have frequently assessed the importance of representation, research in this area has often been siloed by institutional and methodological norms that define academics as “gender”, “race”, or “class” scholars, rather than inclusive scholars of all these and more. This paper thus responds to recent calls for more intersectional work by simultaneously addressing the overlapping representations of race, gender, and gamer identity, and their relation to Lorde’s concept of the mythical norm, in the popular webseries, The Guild (YouTube, 2007-2013). Via a detailed, inductive thematic analysis of the show’s two characters of color, Zaboo and Tinkerballa, we find a doubly problematic intersection between standard “gamer identity” tropes and gendered Asian/American stereotypes. The show forecloses on its potential to be truly diverse and reinforces the oppressive, marginalizing practices it tries to mock, suggesting that gaming culture will not change until we address its intersecting axes of power and exclusion. This research also demonstrates how the constructed identity of media audiences-- in this case, stereotypical “gamer” identity-- can exacerbate and reaffirm existing power disparities in representation. We suggest that media scholars remain attentive to the intersecting articulations of media consumer and individual identities in considering how representation can influence systems of inclusion and exclusion, as well as viewers’ lived outcomes.